Floristic Composition, Structure and Regeneration Status of Riverine Forest at Nech Sar National Park of Ethiopia - Kebebew, Mulugeta; Demissie, Hewan (International Journal of Bio-resource and Stress Management, 2023)
This Study was conducted in Nech Sar National park, Gamo Gofa Zone, Southern Ethiopia from February, 2011−March, 2012 for analyzing floristic composition, structure and regeneration status of woody plant species. The floristic composition and population structure of woody plant species were recorded in 76 quadrats, each of which 20× 20 m2 size. Data on species cover abundance, DBH, height and numbers of individuals per species and altitude were recorded from each quadrat. From NNP Riverine Forest 86 vascular plant species, representing 65 genera and 30 families were recorded. The family Fabaceae had the highest no. of species (11) followed by Euphorbiaceae each with 7 species, Sapindaceae and Tiliaceae each by 5 species. The four most abundant woody plant species in the forest were Lecaniodiscus fraxinifolus, Trichilia dregeana, Syzygium guineense, Euclea divinorum. Moreover, the five most frequently distributed woody plant species were Lecaniodiscus fraxinifolus, Trichilia dregeana, Syzygium guineense, Euclea divinorum and Maytenus senegalensis. Three communities: Lecaniodiscus fraxinifolius-Trichilia dregeana community, Trichilia dregeana-Syzygium guineense community and Syzygium guineense-Lecaniodiscus fraxinifolius community were recognized, with similarity coefficients of 0.65, indicating that there are moderate similarity among the communities. The Shannon-Wiener diversity and evenness in the forest were 2.92 and 0.68 respectively, indicating high diversity. The matured, sapling and seedling density of species were 1815.8(23.3%), 1344.1(17.2%) and 4635.9(59.5%) stems ha-1. The population structure in the forest revealed that there is a need of conservation for communities with poor regeneration status.